Biophysical Studies In Khilau Watershed - Azhary Taufiq; Melya Riniarti; Duryat Duryat; Slamet Budi Yuwono (Universitas Lambung Mangkurat, 2019)
Khilau Watershed (DAS) is one of the sub-watersheds with the status of should be restored. The biophysical conditions of the watershed must be assessed, to determine the suitable actions for land rehabilitation. The purpose of this study was to provide a comparative analysis of baseline data on the biophysical conditions of the Khilau Sub-watershed area based on edaphic and climatic parameters. Data collection method was using cluster sampling in five types of land cover. The data analysis used spatial and laboratory analysis. The results showed that agroforests and annual crops mostly were on moderately steep to steep slopes (15-45%) and all primary forests were in steep slopes (>45%). All the land covers were ultisol. The primary forest has the highest CEC, N-total, P-availability, and C-organic among other land covers. The agroforest has the most acid pH soil among other land covers. The primary forest has the most rapid soil permeability compared to other land covers. The primary forest has the lowest temperature and the highest humidity compared to other land covers